Pricing behavior and non-price characteristics in the airline industry - Peoples, James (Advances in airline economics ;, 2012)
Stepped-up competition in the airline industry over the past 40 years profoundly changed how carriers set fares. Chapters in this volume contribute to our understanding of fare determination in this industry by examining carrier pricing behavior, such as non-linear pricing, pricing decisions associated with strategic alliances, competition from low cost carriers, and the challenges faced by carriers experiencing financial distress. These contributions present nuanced analyses of fare determination that include new ways of examining whether the prices charged by carriers are consumer welfare-enhancing. Examination of airline carrier pricing only tells part of the story of firm behavior, as analysis of carriers' ability to provide quality services is also significant in understanding the economics of this industry. This volume includes chapters examining non-price characteristics of business operations, such as frequency of service, passenger safety, availability of aircraft types for different transportation services, and the geographic distribution of air transportation-related noise by aircraft departures and arrivals at airports.